2016
DOI: 10.1101/049718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two frequency bands contain the most stimulus-related information in visual cortex

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…In both LFP and ECoG, we found high image information in gamma (30 -80 Hz) and lower frequencies (1-12 Hz). Similar results in a free viewing task have been reported previously (Lewis et al, 2016). We observed increased information if these frequencies were combined.…”
Section: Relationship With Previous Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…In both LFP and ECoG, we found high image information in gamma (30 -80 Hz) and lower frequencies (1-12 Hz). Similar results in a free viewing task have been reported previously (Lewis et al, 2016). We observed increased information if these frequencies were combined.…”
Section: Relationship With Previous Studiessupporting
confidence: 92%
“…As seen from Figure 10, this is dominated by the lower frequencies, which led to high overall values for LFP and ECoG accuracies. These results are consistent with a recent study, which showed high image decoding using early response in a free viewing task (Lewis et al, 2016), as well as another study that performed category classification using ECoG signals from humans (Liu et al, 2009). Figure 12 shows the decoding accuracies for late (A) and early (B) periods using FPR.…”
Section: Single-electrode Decoding Performance Across Scalessupporting
confidence: 91%
See 1 more Smart Citation
“…Parts of the data have been used in other publications (Bastos et al, 2015a;Bastos et al, 2015b;Bosman et al, 2012;Brunet et al, 2015;Brunet et al, 2014a;Brunet et al, 2014b;Hindriks et al, 2017;Lewis et al, 2016a;Lewis et al, 2016b;Pinotsis et al, 2014;Richter et al, 2015Richter et al, , 2017Rubehn et al, 2009;Spyropoulos et al, 2017;Vinck et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…We observed that information about the presence of a stimulus (detection decoding), as well as information about stimulus identity (discrimination decoding), were both predominantly conveyed in low (delta-theta) and high (gamma, high-gamma) frequency bands when we considered power and mostly by low frequencies when phase was taken into account, with high frequencies being also informative in some subjects. Interestingly, such a dual timescale profile of neural coding has also been reported in the visual system (Kayser and König, 2004;Belitski et al, 2008;Belitski et al, 2010;Lewis et al, 2016b), suggesting that it might be a general organizational principle of sensory neural processing.…”
Section: Dual Timescale Processing In Auditory Cortexmentioning
confidence: 58%